Eric Brown : a pilot's story - Jones, Nicholas; Austin, Dave (Quanta Films Limited, 2014)
Captain Eric "Winkle" Brown is one of the most accomplished aviators of the 20th century. He has played a major part in the evolution of flight and set records that will never be broken, including flying the largest number of different aircraft (487)and the most aircraft carrier landings (2,407). He recalls his amazing life in this new feature-length documentary. In addition to his legendary career as a test pilot, he was at the 1936 Berlin Olympics, interrogated Hermann Goering, helped liberate the Belsen concentration camp and sang with the Glenn Miller band.